Pengendalian Biaya Produksi Dengan Menggunakan Metode Standar Cost Pada PT. Industri Kereta Api Madiun Tahun 2010 – 2012 - Kartikasari, Diana Ayu; Aisjah, Siti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The rapid development of the Indonesian economy demands that one industry sector to be more competitive in the face of competition. Industry Kereta Api ( Persero ) Madiun is the largest industry and is the only company that makes specialized transportation including trains and in Java and Sumatra. Large industrial companies or automatically have greater financial conditions, this study aims to analyze and evaluate the costs - costs that have come out or in use in the production process and the other using the standard methods of cost and time series. Data used in this study using quantitative data in the form of financial statements. INKA (Persero) Madison during the period of 2010 to 2012. This study on the costs of production that can be controlled with standard costs by calculating the difference in cost. Such differences include the difference in the cost of raw materials, the difference in labor cost and overhead cost difference. Methods of data collection in this study using the method of documentation by evaluating the financial statements and the cost of production. Data analysis techniques used by calculating the difference in the cost of raw materials, the difference in labor costs and excess overhead costs by using the formula with time series from year to year. The results showed that in 2010 and in 2011 production costs for raw materials, labor and factory overhead standard is still in the company, it indicates the year the company was still effective and efficient in managing operating costs, especially in the production. Whereas in 2012 showed that the production costs for raw material costs , labor costs and factory overhead costs have not been sufficient to meet the company's standards, it indicates the year the company is not maximized in Managing production cots. Keywords :Control Cost, Production Cost, Standard Cost Method, and PT INKA ( Persero ) Madiun